Provincial readers in eighteenth-century England - Fergus, Jan S., 1943- (Oxford University Press, 2006)
The English novel took shape in the 18th century, but no one knows who read novels like 'Humphry Clinker' & 'Clarissa' when they were first published. Drawing on booksellers' archives & parish records, this book shows who in the Midlands actually bought novels, plays, & fiction magazines in the 18th century.